Chemical composition of the essential oil from woods of Cunningamia konishii Hayata from Ha Giang - Dai, Do Ngoc; Hung, Nguyen Quang (Academia Journal of Biology, 2013)
The essential oil from wood of Cunninghamia konishii Hayata collected in Tay Con Linh Nature Reserve, Ha Giang province, Vietnam in October 2009 was isolated by steam distillation that give oil yield 0.8% and the oil have analyzed by Capillary GC/MS. Thirty four components were identified those make up more than 97.3% of the total oil. The major essential compounds of the oil consist of α-terpineol (36.6%), α-cedrol (29.8%), cis-α-dehydro terpineol (5.6%), borneol (4.6%), camphor (4.4%) and α-cedrene (3.4%). Less predominant compounds are l-fenchone (1.9%), fenchyl alcohol (1.8%) and α-cadinol (1.0%), and the other compounds were in concentration of less than 0.1-0.9%. A source of α-terpineol, α-cedrol can be exploited in nature. In comparison with essential oil compounds of C. konishii distributed in Pu Mat and Xuan Nha, probably this can be a new chemotyp (chemotyp α-terpineol) of C. konishii in Vietnam.